Overtourism: Insights from Residents of a Himalayan Heritage Hill Station - Tamang, Kushal; Sanmoy, (Turizam, 2025)
Overtourism is a phenomenon that negatively affects a tourist destination's economic, social, and environmental aspects. The problems overtourism reflects are overcrowding, traffic congestion, pollution, and stress on transportation infrastructure. This leads our study to understand the overtourism phenomenon through the residents' perception in a tourist destination of a Himalayan hill station. A descriptive research design is used to explore the problems of overtourism from the residents’ perspective. The data was collected from 148 residents using Google Forms. The study was conducted in Darjeeling, a prominent Himalayan Heritage hill station situated in the northernmost part of the State of West Bengal, India. The study finds that overtourism is a concerning phenomenon, with its effects highly felt by the residents. The results further presented a strong agreement among locals regarding the region's high economic dependency on tourism. Recognising the need for an economically sound and socially acceptable solution. The study proposes a 3R strategic overtourism management model to address overtourism, where 3R stands for Reduce, Replace, and Regenerate. Rather than a strictly linear or sequential strategy, the 3R model for overtourism is conceptualised as a cross-sectional framework in which all three components may co-exist in an integrated manner within a destination’s policy environment. This model proposes three key solutions to mitigating tourism pressure, diversifying tourism as a source of income, and regenerating tourism in a more sustainable manner.